Мотив искушений в драме Флобера «Искушение святого Антония» - Galina Modina (Flaubert: Revue Critique et Génétique)
Many works by Flaubert have autobiographical features, but the author identified himself only with the hero of his philosophical drama The Temptation of saint Anthony. This image accompanied the writer for almost thirty years and arose in Flaubert's manuscripts in turning-points of his life. However, The Temptation of saint Anthony remains one of Flaubert's least read works. in Russian literary criticism. The article tries to discuss Flaubert's text through a prism of the motive of temptation. This motive organizes the drama's artistic space and dominates in each version. However, in early versions (1849, 1856) and in the version completed in 1874, the motive of temptation is developed in special variations. In the early versions of The Temptation of saint Anthony Flaubert aspires to look into and make “visible” the process of transforming the mortal person into the creator. The artist developing is unwrapped as the mystical sacrament similar to the ceremonies of ancient initiations. The drama composition and sequence of episodes are associated with rituals of Eleusinian mysteries and Temptations are represented as a lure to give up the belief in existence of the Creator and in the opportunity of the creative work. The third version is constructed on the development of motives of knowledge and belief, truth and dogma. Here, the sense of temptations consists in the urge to give up seeking the truth. The motive of temptations is indissolubly connected with the artist’s search of identity. Flaubert's internal experience was reflected in three versions of The Temptation of saint Anthony: overcoming the tragical antithesis of the material and the ideal and transferring from Pascal’s mysticism to aesthetic pantheism. The drama can be read as the history of forming the creative individuality of Flaubert, with the temptation being a perquisite for self-knowledge of the Artist.